Petrography of Sandstones of Sirkang Area (Parbat District) Central West Nepal Himalaya (Journal of Nepal Geological Society, 1982)
Different varieties of sandstones are identified from the Lesser Himalayan low grade metasediments of Kali Gandaki Valley. In previous literatures they were very loosely described as quartzites, metasandstones and sandstones. On the basis of a detailed petrographic study, the author has classified these sandstones into five main types, viz. quartz arenite, sublitharenite, feldspathic graywacke, lithic graywacke and dolomitic sandstone; and their paleoenvironmental significance has been discussed. The primary sedimentary textures and structures are strikingly well preserved and the regional metamorphism has caused only mild changes in these rocks.